The Effect of SDG Disclosure, Intellectual Capital, and Institutional Ownership on Financial Performance in Energy Companies Listed on the Indonesia Stock Exchange in 2022–2023 - Yusdian Dwi Aisyah; Nur Isna Inayati; Hadi Pramono; Edi Joko Setyadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to determine the effect of disclosure of Sustainable Development Goals (SDGs), Intellectual Capital (IC), and Institutional Ownership on the financial performance of energy sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2022-2023. This study uses a quantitative method with a sample size of 140 observations obtained from companies' annual reports and sustainability reports. Data analysis in this study was conducted using Stata. The content of the analysis is subject to the author. Intellectual Capital reflects the efficiency and knowledge capacity of companies that utilize their intellectual capital well and tend to be more innovative, a condition that can increase added value for companies. Institutional ownership was chosen to describe corporate governance because investors have greater ability and interest in supervising management, so that corporate decision-making is expected to be more focused. Financial performance in this study was measured using ROA, as it can show how effectively a company manages its assets to generate profits. The results of this study show that the SDGs variable has a positive effect on financial performance, intellectual capital has no effect on financial performance, and institutional ownership also has no effect on financial performance